Revitalizing Village-Owned Enterprises through Micro-Business Empowerment: Strengthening Financial Literacy, Product Design, and Digital Marketing in Yatu Raharja Village, Papua - Meinarni Asnawi; Siti Rofingatun; Rudiawie Larasati; Dereckh Landarsi Aninam; Gilbert A Pelamonia; Rosalia Mistyca Yani; Indri Oktavia Kamma; Marshanda B. Wamafma; Orizanne Inperie Wella Itlay; Herly Asso; Eri Waker (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen the financial literacy, product design, and digital marketing capacity of micro-enterprise owners in Yatu Raharja Village, Arso X District, Keerom Regency, Papua, as an initial step toward revitalizing the long-inactive Village-Owned Enterprise (BUMKam). The program was implemented by the Community Service Team of the Faculty of Economics and Business, Cenderawasih University, in collaboration with the Yatu Raharja Village Government and the local Family Welfare Empowerment (PKK) organization. The intervention involved ten micro-enterprise owners selected through a preliminary household survey conducted alongside a broader community survey involving PKK members. To address the limited availability of laptop computers, two structured mentoring tools—a Simple Selling Price Worksheet and a Manual Business Cashbook—were developed and distributed in printed form. These materials were complemented by Canva-based visual learning resources covering product branding, packaging design, and Instagram content development. Baseline data were analyzed descriptively using percentage distributions and triangulated through SWOT analysis, while program outcomes were evaluated qualitatively through participatory observation and reflective discussions conducted during two mentoring sessions. The findings indicated improvements in participants' ability to apply cost-based pricing, increased commitment to maintaining routine financial records, and strong interest in using Instagram as a promotional platform. These outcomes were assessed through participatory observation rather than standardized pre- and post-intervention testing. Overall, these findings suggest that context-sensitive mentoring supported by practical learning tools can strengthen the entrepreneurial capacity of rural micro-enterprises and provide a foundation for the phased revitalization of the Yatu Raharja Village-Owned Enterprise (BUMKam).